Entre inscrições e escrições : a poética de Wlademir Dias-Pino - Leria, Andreza Moraes Branco (2015)
The purpose of this research is to analyze the aesthetic / informational proposed production in the book-catalog: SEPARATION BETWEEN REGISTER AND WRITE, of Dias-Pino, published in 1982, from: the process of "de-realization" of the word; the expansion of blank spaces on the page; the way to the death of the verse, inserting and resizing of national and international vanguard of written text of dilution; the autonomy of the text and participatory reader; the importance of the project for triggering the process . We selected some poems that gave visibility to the serial production process understanding that these poems have as a starting point an array. Sought still place greater emphasis on visual poems that do not have a great critical fortune and that enabled us both literary analysis and the construction of a certain identity. From these elements, we note the importance of registration for the purposes of poetic resulting in an immense poetic kaleidoscope. This objective considers that artistic and literary intervention should respond radicalized way to new paradigms imposed by contemporaneity. The trials, which paradoxically go beyond rules and pre-established formulas appreciate the playful and creative freedom process. The Poem-Process is a "poem to be seen, not to be read. With this practice, Wlademir Dias-Pino imposes not only a new concept of literature, but also the idea of the work as physicality "(Magalhães, 2001, p.203). It can be said that the visuality and physicality are embedded in the contemporary world and are an important and integral component elements of the socio-cultural relations is therefore in this perspective that is part and highlights the production Dias-Pino.